The Success of Preaching Amid Gender Issues - Giska Lovina (State Institute of Islamic Studies Batusangkar, 2023)
Preaching in the era of globalization has become an essential aspect of human life transformation. Humans, with their complex nature, must be capable of adapting to an increasingly dynamic era. Gender differences should ideally enable religious individuals to embrace diversity, which supports success in the preaching process. However, in its actualization within society, the presence of gender differences becomes an inevitable issue and problematic. Preaching for every steward of the Earth will only succeed if gender equality issues are not brought up.